Unusual Malposition of a Chest Tube, Intrathoracic but Extrapleural - Alqasem Fuad H. Al Mosa; Mohammed Ishaq; Mohamed Hussein Mohamed Ahmed (Case Reports in Radiology)
Chest tube malpositioning is reported to be the most common complication associated with tube thoracostomy. Intraparenchymal and intrafissural malpositions are the most commonly reported tube sites. We present a case about a 21-year-old patient with cystic fibrosis who was admitted due to bronchiectasis exacerbation and developed a right-sided pneumothorax for which a chest tube was inserted. Partial initial improvement in the pneumothorax was noted on the chest radiograph, after which the chest tube stopped functioning and the pneumothorax remained for 19 days. Chest computed tomography was done and revealed a malpositioned chest tube in the right side located inside the thoracic cavity but outside the pleural cavity (intrathoracic, extrapleural). The removed chest tube was patent with no obstructing materials in its lumen. A new thoracostomy tube was inserted and complete resolution of the pneumothorax followed.